Ecosystem size matters: the dimensionality of intralacustrine diversification in Icelandic stickleback is predicted by lake size. Issue 15 (29th June 2016) - Lucek, Kay; Kristjánsson, Bjarni K.; Skúlason, Skúli; Seehausen, Ole
Abstract: Cases of evolutionary diversification can be characterized along a continuum from weak to strong genetic and phenotypic differentiation. Several factors may facilitate or constrain the differentiation process. Comparative analyses of replicates of the same taxon at different stages of differentiation can be useful to identify these factors. We estimated the number of distinct phenotypic groups in three‐spine stickleback populations from nine lakes in Iceland and in one marine population. Using the inferred number of phenotypic groups in each lake, genetic divergence from the marine population, and physical lake and landscape variables, we tested whether ecosystem size, approximated by lake size and depth, or isolation from the ancestral marine gene pool predicts the occurrence and the extent of phenotypic and genetic diversification within lakes. We find intralacustrine phenotypic diversification to be the rule rather than the exception, occurring in all but the youngest lake population and being manifest in ecologically important phenotypic traits. Neutral genetic data further indicate nonrandom mating in four of nine studied lakes, and restricted gene flow between sympatric phenotypic groups in two. Although neither the phenotypic variation nor the number of intralacustrine phenotypic groups was associated with any of our environmental variables, the number of phenotypic traits that were differentiated was significantly positively related to lake size, and evidence for restricted gene flow between sympatric phenotypic groups was only found in the largest lakes where trait specific phenotypic differentiation was highest. Abstract : We estimated the number of distinct phenotypic groups in three‐spine stickleback populations from nine lakes in Iceland and in one marine population to test whether ecosystem size, approximated by lake size and depth, or isolation from the ancestral marine gene pool may predict the occurrence and the extent of phenotypic and genetic diversification within lakes. We find intralacustrine phenotypic diversification to be the rule rather than the exception, occurring in all but the youngest lake population and differing in ecologically important phenotypic traits. We find the dimensionality of phenotypic differentiation to be positively related to lake size, but evidence for restricted gene flow between sympatric phenotypic groups was only found in the largest lakes where phenotypic differentiation was highly dimensional.